Health-Related Quality of Life and Outcome after Total Knee Replacement: Results from a Cross-Sectional Survey in Jordan. (10th December 2021) - Al Thaher, Yazan; Alfuqaha, Othman A.; Dweidari, Ahmed
Abstract : Total knee replacement (TKR) is a common procedure that is considered cost-effective with excellent long-term survivorship. This cross-sectional study, which includes 118 selected patients in Jordan from January 2020 to January 2021, aims to assess health-related quality of life (HQOL), functional status, and associated factors before and after 3 to 12 months of TKR. Furthermore, several demographical factors were included in this study to evaluate the potential association with the procedure's outcome. Western Ontario and McMaster Universities Osteoarthritis Index scale (WOMAC) and Short Form-36 (SF-36) scale were used in this study. It was found that the main change occurred 6–12 months after the procedure. Gender and age were found to be the primary predictor of quality of life among TKR patients. Patients before the TKR procedure experienced severe pain, joint stiffness, physical impairment, and psychological demand issues. After the TKR procedure, all symptoms were improved significantly. The TKR procedure can improve the quality of life for patients, which can be detected for several months after the procedure. Function and pain are the most critical indicators of improvement in quality of life. Assessing the quality of life is a key indicator for identifying patients without improvement, as well as improving the health care process and comparing other alternative interventions.